Effects of coaxial dielectric barrier discharge on water treatment at different sites of Kathmandu Valley, Nepal - Gyawali, Hari Prasad; Shrestha, J.; Nakarmi, N.; Tyata, R.B. (Journal of Science and Engineering, 2018)
The research work reports the results concerning the effects of ozone produced by dielectric barrier discharge (DBD) in well, river and industrial wastewater. The dielectric barrier discharge (DBD) unit was developed to produce highly oxidizing ozone molecules, hydrogen peroxide and hydroxyl radicals for the treatment of water. The discharge was produced by applying AC high voltage (up to 10 kV peak-to-peaks) source of frequency 26 kHz across annular electrodes. The well and wastewater samples were collected from 5 different places of Kathmandu district, Nepal. Various physical, chemical and micro-biological parameters such as pH, Electrical Conductivity (EC), Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Coliform were analysed before and after ozonation. Our results showed that pH of water after treatment changed slightly with respect to pH of untreated water. There was slight change in conductivity of water from the different sources after treatment by ozone. DO of all samples increased significantly after ozonation. It was found that BOD and COD of all samples decreased significantly after ozonation. Concentration of ferrous ion (Fe2+) decreased after ozonation. There was significant decrease in Total Coliform after treatment.